A rapid review of studies on COVID-19 and gender equality in agriculture - Puskur, Ranjitha; D’Souza, Judith (CGIAR GENDER Impact Platform, 2020)
Research on COVID-19 and the social, economic, food and health ramifications of this pandemic is rapidly emerging from many disciplines. There is strong evidence from reports, peer-reviewed papers and working papers demonstrating the disproportionately negative economic impact of COVID-19 on women compared to men. Concerns about roll back of advances in gender equality and the gendered impacts of the pandemic have been raised from its early stages and research is increasingly beginning to consider the role gender plays in these relationships. Gendered impacts of COVID-19 included an increase in violence against women, unpaid labor, disproportionate levels of unemployment, and increased barriers to ensuring food and nutrition security and food systems for the vulnerable and marginalized communities globally.